Inversion Based Accuracy Comparison of Non-hyperbolic Moveout Approximations for P-waves in VTI Media - Asgharzadeh, Mehdi; Nadri, D.; Bona, Andrej (EAGE, 2014)
In this study we have quantified the accuracy of six most common non-hyperbolic traveltime approximations for P-waves in VTI media in terms of medium anisotropy and ratio of the maximum source offset to reflector depth. Our analysis is based on the inversion of P-wave traveltimes for VTI anisotropy parameters of the medium as we believe that the accuracy of the inversion results is directly related to the accuracy of traveltime approximation. Our analysis shows that among all, only approximation presented by Fomel and Stovas (2010) has enough accuracy to produce reliable estimates of VTI anisotropy parameters for both a wide range of medium anisotropy and wide offset /depth ratios.